Measurement errors on sediment concentration from traditional runoff collection tanks and its correction possibility - Huang, Yuhan; Zhao, Hui; Li, Fahu; Yuan, Pujin; Wang, Wei; Zhang, Guanghui (International Journal of Agricultural and Biological Engineering, 2019)
Runoff plots are widely used worldwide to monitor water and soil losses. Sediment concentration in runoff collection tank is measured by stirring-sampling procedure, but this method may produce high measurement error due to the uneven mixing of collected sediments with water and soil particle deposition. This study aimed to identify the relationship between actual and measured sediment concentrations, so as to estimate the systematic error of sediment concentration measurement from runoff collection tank by traditional stirring-sampling procedure and the possibility to eliminate it. Four major soils including black soil, silt loess, clay loess, and purple soil in China were used to determine the correlation between the measured and designed sediment concentrations in laboratory. Tested sediment concentration was 1, 2, 5, 8, 10, 20, 50, 80, 100, 200, 500, 800, and 1000 kg/m3, and total sediment-laden water volume was 50 L and 100 L. Five samples were collected successively from collection tank for each treatment and their sediment concentrations were measured by conventional oven-drying method. The results showed that all the measured sediment concentration values were smaller than the designed ones, but both the measured and designed values were linearly correlated significantly with determination coefficients greater than 0.8, generally. In the whole tested concentration range, the systematical error was –0.19 to –319.95 kg/m3 and relative error was 0.30%-84.5% for the 4 tested soils and 2 total sediment-laden water volumes. These results indicated a necessity and possibility to correct conventional sediment concentration measurement value. The result is usable to assess and correct the measurement error of sediment concentrations from traditional runoff plot. Keywords: collection tank, measurement error, runoff plot, sediment concentration, stirring-sampling method DOI: 10.25165/j.ijabe.20191203.4208 Citation: Huang Y H, Zhao H, Li F H, Yuan P J, Wang W, Zhang G H. Measurement errors on sediment concentration from traditional runoff collection tanks and its correction possibility. Int J Agric & Biol Eng, 2019; 12(3): 77–83.